Effect of thymol on kinetic properties of Ca and K currents in rat skeletal muscle - Szentandrássy, Norbert (BioMed Central, 2003)
BACKGROUND: Thymol is widely used as a general antiseptic and antioxidant compound in the medical practice and industry, and also as a stabilizer to several therapeutic agents, including halothane. Thus intoxication with thymol may occur in case of ingestion or improper anesthesia. In the present study, therefore, concentration-dependent effects of thymol (30–600 micro-grams) were studied on calcium and potassium currents in enzymatically isolated rat skeletal muscle fibers using the double vaseline gap voltage clamp technique. RESULTS: Thymol suppressed both Ca and K currents in a concentration-dependent manner, the EC(50 )values were 193 ± 26 and 93 ± 11 μM, with Hill coefficients of 2.52 ± 0.29 and 1.51 ± 0.18, respectively. Thymol had a biphasic effect on Ca current kinetics: time to peak current and the time constant for inactivation increased at lower (100–200 μM) but decreased below their control values at higher (600 μM) concentrations. Inactivation of K current was also significantly accelerated by thymol (200–300 μM). These effects of thymol developed rapidly and were partially reversible. In spite of the marked effects on the time-dependent properties, thymol caused no change in the current-voltage relationship of Ca and K peak currents. CONCLUSIONS: Present results revealed marked suppression of Ca and K currents in skeletal muscle, similar to results obtained previously in cardiac cells. Furthermore, it is possible that part of the suppressive effects of halothane on Ca and K currents, observed experimentally, may be attributed to the concomitant presence of thymol in the superfusate.